2016
DOI: 10.1186/s40064-016-1954-6
|View full text |Cite
|
Sign up to set email alerts
|

Response-adapted treatment with upfront high-dose chemotherapy followed by autologous stem-cell transplantation rescue or consolidation phase high-dose methotrexate for primary central nervous system lymphoma: a long-term mono-center study

Abstract: Treatment regimens for primary central nervous system lymphoma (PCNSL) include high-dose methotrexate (HD-MTX)-based chemotherapy, with or without radiotherapy and are based on studies of selected patient groups. This retrospective study assessed a consistent strategy of response-adapted protocol applied for patients including age >65 years in a cancer center for 10 years longitudinally. Case notes were studied of 61 consecutively treated patients with PCNSL histologically diagnosed between 2003 and 2013. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Rubenstein et al ( 5 ) conducted a study of high-dose chemotherapy consolidation in PCNSL with etoposide plus cytarabine (EA) (CALGB 50202) offering another consolidation treatment option in PCNSL without episodes of grade 3 or 4 neurotoxicity in consolidation. In agreement with CALGB 50202 and a few other retrospective studies ( 26 , 27 ), our results showed that nonmyeloablative consolidation chemotherapy was feasible in PCNSL patients who achieved CR after first-line IC. The 2-year time to progression was longer in the report of Rubenstein than ours, which may be due to the exclusion of patients with PS larger than 2 in clinical trials.…”
Section: Discussionsupporting
confidence: 91%
“…Rubenstein et al ( 5 ) conducted a study of high-dose chemotherapy consolidation in PCNSL with etoposide plus cytarabine (EA) (CALGB 50202) offering another consolidation treatment option in PCNSL without episodes of grade 3 or 4 neurotoxicity in consolidation. In agreement with CALGB 50202 and a few other retrospective studies ( 26 , 27 ), our results showed that nonmyeloablative consolidation chemotherapy was feasible in PCNSL patients who achieved CR after first-line IC. The 2-year time to progression was longer in the report of Rubenstein than ours, which may be due to the exclusion of patients with PS larger than 2 in clinical trials.…”
Section: Discussionsupporting
confidence: 91%
“…Stem cell transplantation is an innovative treatment strategy that utilizes autologous stem cells to serve as a rescue therapy after high-dose chemotherapy (1). In patients with life-threatening disease, such as hematologic malignancies and inborn errors of metabolism or the immunodeficiency allogeneic stem cell transplantation is a conceivable curative treatment (2).…”
Section: Introductionmentioning
confidence: 99%
“…In total we identified five completed [32,42,43,45,49,50] and one ongoing RCT [29], 26 prospective studies (two with control [67,69], 24 single arm studies [31,[55][56][57][58][59][60][61][62][63][64][65][66]68,[70][71][72][73][74][75][76][77][78][79] and 24 retrospective studies (with or without control) [17,30,37,45,[80][81][82][83][84][85][86][87][88][89][90][91][92]…”
Section: Discussionmentioning
confidence: 99%